Investigating language teachers' ideals in images and interviews. (April 2021) - Stickler, Ursula
Abstract: Ideals have been linked to identity, motivation and stamina. To investigate language teachers' ideals in depth, this study employs a novel complex, three-step method, analysing data collected through drawings and one-to-one reflective interviews with a voice centred relational method (VCRM) for analysis. VCRM conserves the interviewees' personal voice and includes the researcher as part of the process of analysis. This paper will show how the complex method can be employed and how the findings derived from it allow insights into the forces that keep teachers going, their origins, and their potential for integrating change. Thus, qualitative data collection methods combined with a voice-centred analysis method can be harnessed to enhance our understanding of teacher ideals and the tensions between external demands, internal standards, and different cultures language teachers have to cope with.